Towards an engaging and gamified online learning environment - a real case study - Portela, Filipe (2022)
Currently, remote work is common, and this trend has come to several areas and processes, such as education and teaching. Regarding higher education, universities have several challenges to overcome, the most challenging being transforming teaching to be more digital and engaging. Therefore, TechTeach has arisen as a new teaching paradigm that creates a unique learning environment and satisfies students’ and professors’ expectations. After the success of the b-learning approach, professors created new experiences utilizing an entirely online learning environment following this paradigm. This article shows the work performed through a real case study, explains the strategy used to implement this paradigm, provides students’ opinions, and analyses the results achieved. The results demonstrated that, while the effort was tremendous, the result was beneficial to all. After 208 online hours of classes, 11,173 downloads, 15,224 messages, 200,000 sessions, 3 rescues requests, and 28t cards, 98.15% of the active participants gave it their approval, 96.53% considered this subject equal to or better than the others, and 85% of accepted the gamification system. These results show that a class can be an engaging environment where students can learn and enjoy it regardless of whether it is physical or not.